Effects of an offshore sailing competition on anthropometry, muscular performance, subjective wellness, and salivary cortisol in professional sailors - Philippe, K.; Paillard, T.; Maurelli, O.; Moody, J.; Prioux, J. (International Journal of Sports Physiology and Performance, 2022)
Introduction: Evidence regarding the impact of offshore sailing on fatigue and readiness variables is conspicuous by its absence. This study investigated the acute effects of an offshore sailing regatta on anthropometry, muscular performance, subjective recovery, and salivary biomarker cortisol. Methods: Ten professional offshore sailors from a mixed-sex crew partook in the study (N = 10; mean [SD] age = 32.2 [3.96] y; stature = 179.1 [7.30] cm; body mass = 84.2 [12.1] kg). The race involved 3 offshore legs over a 3-week period. Baseline measures of anthropometry, lower- and upper-body muscular function, perceptions of subjective wellness, and salivary cortisol were assessed 3 hours prior to competition (ie, before the first leg). These measures were repeated within 30 minutes after the cessation of each leg. During each leg, boat movements were recorded via global positioning system units.